Analisis Representasi Trauma dan Mekanisme Koping dalam Film "The Batman" (2022): Studi Psikologis Karakter Bruce Wayne dalam Era Kontemporer: Penelitian - Nova Lisye Sinaulan; Marssel Michael Sengkey; Trilan Hugo Iswandi Sinurat; Virthita Gisela Natalie Tanor; Refanly Imanuel Tampongangoy; Virgin Christmas Wariki (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the representation of psychological trauma and coping mechanisms in Matt Reeves' film The Batman (2022), highlighting Robert Pattinson's interpretation of the character Bruce Wayne as a figure grappling with unresolved childhood trauma. Through a cinematic and psychological approach, the film presents the most realistic and profound portrayal of the psychological impact of the tragic loss of a parent, depicting Wayne as an individual suffering from chronic insomnia, extreme social isolation, emotional numbing, hypervigilance, and difficulty forming interpersonal relationships—symptoms characteristic of PTSD. The Batman identity is used as a maladaptive coping mechanism, serving as an escape from healthy grief processing and reinforcing the trauma cycle through obsessive compulsions toward justice and destructive revenge fantasies. Wayne's relationships with Alfred, Selina Kyle, and Commissioner Gordon reflect issues of emotional attachment and fear of rejection rooted in the loss of parental figures, while the narrative parallels between Batman and the Riddler highlight the concept of inherited trauma and how individuals with similar inner wounds can develop vastly different coping strategies.